Neuraxial anesthesia is associated with improved survival after total joint arthroplasty depending on frailty: a cohort study. Issue 6 (7th April 2020) - Johnson, Rebecca L; Frank, Ryan D; Habermann, Elizabeth B; Chamberlain, Alanna M; Abdel, Matthew P; Schroeder, Darrell R; Mantilla, Carlos B
Abstract : Background: Frailty increases risk for complications after total joint arthroplasty (TJA). Whether this association is influenced by anesthetic administered is unknown. We hypothesized that use of neuraxial (spinal or epidural) anesthesia is associated with better outcomes compared with general anesthesia, and that the effect of anesthesia type on outcomes differs by frailty status. Methods: This single-institution cohort study included all patients (≥50 years) from January 2005 through December 2016 undergoing unilateral, primary and revision TJA. Using multivariable Cox regression, we assessed relationships between anesthesia type, a preoperative frailty deficit index (FI) categorized as non-frail (FI <0.11), vulnerable (FI 0.11 to 0.20), and frail (FI >0.20), and complications (mortality, infection, wound complications/hematoma, reoperation, dislocation, and periprosthetic fracture) within 1 year after surgery. Interactions between anesthesia type and frailty were tested, and stratified models were presented when an interaction (p<0.1) was observed. Results: Among 18 458 patients undergoing TJA, more patients were classified as frail (21.5%) and vulnerable (36.2%) than non-frail (42.3%). Anesthesia type was not associated with complications after adjusting for age, joint, and revision type. However, in analyzes stratified by frailty, vulnerable patients under neuraxial block had less mortality (HR=0.49; 95% CI 0.27 to 0.89) and wound complications/hematoma (HR=0.71; 95% CI 0.55 to 0.90), whereas no difference in risk by anesthesia type was observed among patients found non-frail or frail. Conclusions: Neuraxial anesthesia use among vulnerable patients was associated with improved survival and less wound complications. Calculating preoperative frailty prior to TJA informs perioperative risk and enhances shared-decision making for selection of anesthesia type.